Improved crush energy absorption in 3D woven composites by pick density modification. (1st July 2020) - Neale, Geoffrey; Dahale, Monali; Yoo, Sanghyun; Toso, Nathalie; McGarrigle, Cormac; Quinn, Justin; Kelly, John; McIlhagger, Alistair; Archer, Edward; Harkin-Jones, Eileen
Abstract: Although 3D woven composites have exceptional out-of-plane properties, there is a lack of understanding for these materials in crash application in automotive and aerospace industries. To encourage the use of 3D wovens in crashworthy automotive structures, knowledge must be gained so that designers can adjust the highly flexible weave parameters to create tailor-made performance materials. Here we show that fabric pick density causes large changes in progressive failure modes and associated energy absorption, particularly in the dynamic regime, where the quasi-static to dynamic energy absorption loss typical of composites is completely removed. Compression and flexure properties, which are known to be linked to crash performance in composites, are also investigated for these 3D woven layer-to-layer interlock carbon-epoxy composite structures. 3D fabric preforms are manufactured in three different pick densities: 4, 10 & 16 wefts/cm. With a constant warp density of 12 warps/cm from carbon fibres. Increasing the pick density improved specific energy absorption (SEA) even in relatively inefficient progressive failure modes like folding, which has not previously observed in composite materials. SEA values up to 104 J/g (quasi-static) and 93 J/g (dynamic) are recorded. This work shows that minor weft direction (transverse) weave changes can lead to sizeable improvements in warp direction (axial) energy absorption without fundamentally redesigning the weave architecture.